Предмет: Математика, автор: u83557060

ПОМОГИТЕ ПОЖАЛУЙСТА СРОЧНО​

Приложения:

Ответы

Автор ответа: dyexfnf
1

Ответ:

Пошаговое объяснение:

1.(5а⁴ + 3а²b - b²) - (3а⁴ + 4а²b - b²) = 5а⁴ + 3а²b - b² - 3а⁴ - 4а²b + b² =

= 2а⁴ - а²b

2.(12ху - 10х² + 9у²) - (-14х² + 9ху - 14у²) =

= 12ху - 10х² + 9у² + 14х² - 9ху + 14у² = 3ху + 4х² + 23у²

3. (7ab² - 8ab + 4a²b) + (10ab - 7a²b) = 7ab² - 8ab + 4a²b + 10ab - 7a²b =

= 7ab² + 2ab - 3a²b

4.(2с² + 3с) + (-с² + с) - (с² + 4с - 1) = 2с² + 3с - с² + с - с² - 4с + 1 = 1

Похожие вопросы